Single-chip, mid-infrared array for room temperature video rate imaging - Xie, Chengzhi; Aziz, Mohsin; Pusino, Vincenzo; Khalid, Ata; Steer, Matthew; Thayne, Iain G.; Sorel, Marc; Cumming, David R. S. (The Optical Society, 2017)
The need for energy efficiency and lower emissions from industrial plants and infrastructures is driving research into novel sensor technologies, especially those that allow observing and measuring greenhouse gases, such as CO2CO2. CO2CO2 emissions can be captured using mid-infrared imagers, but at present, these are based on hybrid technologies that need expensive manufacturing and require cooling. The high price tag prevents a wider diffusion of mid-infrared imagers and hence their use for many low-cost and large-volume applications. Here we report a monolithic III-V technology that integrates GaAs transistors with an InSb photodiode array. The monolithic material system reduces costs and provides an excellent platform for the sensor system-on-chip. We present a focal plane array imaging technology operating at room temperature in the 3–6 μm wavelength range that will address the need for identification and measurement of a range of industrially important gases.